Terahertz band communication systems: Challenges, novelties and standardization efforts - Tekbiyik, Kursat; Ekti, Ali Riza; Kurt, Gunes Karabulut; Gorcin, Ali (ELSEVIER, 2019)
Wireless data rates are expected to be around 10Gbps or even more within the upcoming decade. The realization of such high data rates is unlikely with the currently licensed bands in the spectrum. Therefore, it is clear that such high rates could only be achieved by employing more bandwidth with the state-of-the-art technology. Considering the fact that bands in the range of 275GHz-3000GHz, which are known as Terahertz (THz) bands, are not yet allocated for specific active services around the globe, there can be a true potential to achieve the desired data rates at THz bands. However, due to the characteristics of these bands, there are many open issues in terms of THz radio communication system design. In this study, open issues and the state-of-the-art solutions to these issues for THz communication system design are discussed. Moreover, standardization efforts up to date are elaborated. This study concludes that the actual implementation of fully operational THz communication systems obliges to carry out a multi-disciplinary effort including statistical propagation and channel characterizations, adaptive transceiver designs (including both baseband and radio frequency (RF) front-end portions), reconfigurable platforms, advanced signal processing algorithms and techniques along with upper layer protocols equipped with various security and privacy levels. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Terahertz; Beyond 5G wireless communication; Nanonetworks; Terahertz hardware; Graphene; WIRELESS NANOSENSOR NETWORKS; QUANTUM CASCADE LASERS; THZ COMMUNICATIONS; DATA-TRANSMISSION; MILLIMETER-WAVE; BROAD-BAND; ELECTROMAGNETIC NANONETWORKS; MAGNETIC NANOPARTICLES; NANO-COMMUNICATION; CHANNEL MODEL; Engineering; Telecommunications